2018
DOI: 10.31807/tjwsm.363608
|View full text |Cite
|
Sign up to set email alerts
|

Biological Assessment of Water Quality: Ecological Status of Three Aegean Reservoirs Based on Phytoplankton Metrics

Abstract: Assessing freshwater quality is getting more important since the implementation of the European Union Water Framework Directive. In the present study, the water quality of three reservoirs of the North Aegean basin of Turkey was assessed using Mediterranean Phytoplankton Trophic Index and Phytoplankton Trophic Index. Data were collected seasonally between summer 2014 and summer 2015 from three reservoirs. The reservoirs showed alkaline waters. The highest nutrients values of TP (203.5 µg L-1) at Bayramiç Reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…For IPS, EPI‐D, IBD and TDIL, the class boundaries of Eloranta and Soininen (2002) and Dumnicka et al (2006) were used for the ecological status assessment of the lentic systems. Class boundaries of TIT and EPI‐L were used according to Çelekli et al (2017) and Marchetto et al (2013), respectively, for the quality assessment of studied lentic systems.…”
Section: Methodsmentioning
confidence: 99%
“…For IPS, EPI‐D, IBD and TDIL, the class boundaries of Eloranta and Soininen (2002) and Dumnicka et al (2006) were used for the ecological status assessment of the lentic systems. Class boundaries of TIT and EPI‐L were used according to Çelekli et al (2017) and Marchetto et al (2013), respectively, for the quality assessment of studied lentic systems.…”
Section: Methodsmentioning
confidence: 99%
“…Trophic Index Türkiye (TIT) was calculated according to Toudjani et al (2017), Çelekli et al (2017) and Çelekli, Toudjani, et al (2019). ‘OMNIDIA’ program (Lecointe et al, 1993) was used to calculate different diatom indices such as Artois‐Picardie Diatom Index (IDAP) (Prygiel et al, 1996), Eutrophication/Pollution Index (EPI‐D) (Dell'Uomo, 2004), Biological Diatom Index (IBD) (Coste et al, 2009), Steinberg and Schiefele's Index (SHE) (Steinberg & Schiefele, 1988), Swiss Diatom Index (DICH) (Hürlimann & Niederhauser, 2002), Watanabe Index (WAT) (Watanabe et al, 1990), Specific Pollution Sensitivity Index (IPS) (Cemagref, 1982), Sládeček's Index (SLA) (Sládeček, 1986), Descy's Index (DES) (Descy, 1979), Leclercq and Maquet Diatomic Index (IDSE) (Leclercq & Maquet, 1987), Generic Diatom Index (IDG) (Rumeau & Coste, 1988), Metric‐European Index (CEE) (Descy & Coste, 1991), Trophic Diatom Index (TDI) (Kelly & Whitton, 1995), Trophic‐Saprobic Index (LOBO) (Lobo et al, 2004), Pampean Diatom Index (IDP) (Gómez & Licursi, 2001), Rott's Saprobic Index (ROTTs) (Rott et al, 1997) and Rott's Trophic Index (ROTTt) (Rott et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies have shown that diatom composition and abundance vary by geographic region (Soininen et al, 2019) and that regional factors such as climate, geology and land use are important for the diatom community (Pajunen et al, 2016; Soininen, 2007). In recent years, like many other countries, the Trophic Index Türkiye (TIT) was developed because of the need to use a region‐specific diatom index and the increasing number of water quality studies in Türkiye (Çelekli et al, 2017; Çelekli, Toudjani, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytoplankton, macrophyte and phytobenthos, benthic invertebrates and fish are the biological quality elements for the classification of ecological status (Anonymous, 2000). There are some studies (Demir et al, 2017;Çelekli et al, 2018;Solak et al, 2018a) for identifying the ecological status of water bodies in Turkey within the scope of the river basin based monitoring studies.…”
Section: Introductionmentioning
confidence: 99%